RECOGNITION APPLICATION FORM, FUNCTION AND DISEASE DENTAL WEB-BASED USING MACROMEDIA FLASH MX 2004 - Septiyani Septiyani; Yulina Yulina,Skom, MMSi (Jurnal Sistem Informasi, 2008)
Introduction to manufacturing applications in Form, Function and Dental Disease is authors using Macromedia Flash MX 2004. This application is made with the purpose of providing information to the children and communities about the importance of maintaining healthy teeth. Recognition application program form, function and dental disease and a web-based multimedia made easier and make users more interested to find out.